Improving total body irradiation with a dedicated couch and 3D-printed patient-specific lung blocks: A feasibility study - Strolin, Silvia; Paolani, Giulia; Santoro, Miriam; Cercenelli, Laura; Bortolani, Barbara; Ammendolia, Ilario; Cammelli, Silvia; Cicoria, Gianfranco; Win, Phyo Wai; Morganti, Alessio G.; Marcelli, Emanuela; Strigari, Lidia (Frontiers in Oncology, 2023)
Introduction: Total body irradiation (TBI) is an important component of the conditioning regimen in patients undergoing hematopoietic stem cell transplants. TBI is used in very few patients and therefore it is generally delivered with standard linear accelerators (Linacs) and not with dedicated devices. Severe pulmonary toxicity is the most common adverse effect after TBI, and patient-specific lead blocks are used to reduce the mean lung dose. In this context, an online treatment setup is crucial to achieve precise positioning of the lung blocks. Therefore, in this study, we aim to report our experience at generating 3D printed patient-specific lung blocks and coupling a dedicated couch (with an integrated onboard image device) with a modern Linac for TBI treatment. Results: 3D printing of lung blocks was feasible for all planned patients using a stereolithography 3D printer with a build volume of 14.5×14.5×17.5 cm3. The number of required pre-TBI EPID-images generally decreases after the first fraction. In patient-specific QA, the difference between measured and calculated dose was generally <2%. The MOSFET measurements reproducibility along each treatment and patient was 2.7%, in average. Conclusion: The TBI technique was successfully implemented, demonstrating that our approach is feasible, flexible, and cost-effective. The use of 3D printed patient-specific lung blocks has the potential to personalize TBI treatment and to refine the shape of the blocks before delivery, making them extremely versatile.